Bis (Diamines) Cu and Zn Complexes of Flurbiprofen as Potential Cholinesterase Inhibitors: In Vitro Studies and Docking Simulations - Muhammad Jamil; Nargis Sultana; Rizwan Ashraf; Maryam Bashir; Muhammad Fayyaz ur Rehman; Fariha Kanwal; Humna Ellahi; Changrui Lu; Wei Xing Zhang; Muhammad Ilyas Tariq (Crystals, 2021)
Alzheimer’s disease (AD) causes dementia and continuous damage to brain cells. Cholinesterase inhibitors can alleviate the condition by increasing communication between the nerve cells and reducing the risk of dementia. In an effort to treat Alzheimer’s disease, we synthesized flurbiprofen-based diamines (1,2 diaminoethane and 1,3 diaminopropane) Zn(II), Cu(II) metal complexes and characterized them by single-crystal X-ray analysis, NMR, (FT)-IR, UV-Vis, magnetic susceptibility, elemental analysis and conductivities measurements. Synthesized diamine metal complexes appeared in ionic forms and have distorted octahedral geometry based on conductivity studies, magnetic susceptibility and electronic studies. Single crystal X-ray diffraction analysis confirmed (2b) Cu(H2O)2(L1)2(L2)2 complex formation. Moreover, we tested all synthesized metal complexes against the cholinesterase enzyme that showed higher inhibition potential. In general, copper metal complexes showed higher inhibitory activities than simple metal complexes with flurbiprofen. These synthesized metal complexes may derive more effective and safe inhibitors for cholinesterases.